MicroRNAs in endometrial cancer - Yanokura, Megumi; Banno, Kouji; Iida, Miho; Irie, Haruko; Umene, Kiyoko; Masuda, Kenta; Kobayashi, Yusuke; Tominaga, Eiichiro; Aoki, Daisuke (Technische Universität Dortmund, 2015)
Endometrial cancer is a common malignant gynecological tumor, but there are few biomarkers that are useful for early and accurate diagnosis and few treatments other than surgery. However, use of microRNAs (miRNAs) that induces gene downregulation in cells may permit effective and minimally invasive diagnosis and treatment. In endometrial cancer cells, expression levels of miRNAs including miR-185, miR-210 and miR-423 are upregulated and those of miR-let7e, miR-30c and miR-221 are downregulated compared to normal tissues, and these miRNAs are involved in carcinogenesis, invasion and metastasis. miRNAs with expression changes such as miR-181b, miR-324-3p and miR-518b may be used as prognostic biomarkers and transfection of miR-152 may inhibit cancer growth. However, most current studies of miRNAs are at a basic level and further work is needed to establish clinical applications targeting miRNAs.
recent advances and potential clinical applications
EXCLI Journal ; Vol. 14, 2015
Keywords: microRNA; endometrial cancer; biomarker; OncomiR; tumor suppressor miR; 610